DATA MANAGEMENT OF POSYANDU MANAGEMENT INFORMATION SYSTEM INTEGRATION OF PRIMARY CARE SERVICES (ILP) IN KARANGREJO VILLAGE, NGASEM DISTRICT, KEDIRI REGENCY IN 2024 - Aris Dwi C; Luluk S.; Fannidya HZ; Suryono (Pedagogic Research-Applied Literacy Journal, 2025)
The Integrated Primary Care Integration Posyandu (ILP) activity is a health service activity that aims to strengthen health services in village community areas. This activity is carried out in the form of screening for non-communicable diseases. ILP Posyandu is held once a month and on average is managed by 5-6 cadres. Activities carried out include screening for non-communicable diseases such as checking blood pressure, checking abdominal circumference, checking blood sugar, health education and providing additional food to PMT Toddlers, Teenagers and PMT Elderly. The recording and data collection process is still carried out manually using a ledger which is then recapitulated and becomes a database for reporting ILP Posyandu activities to the relevant units. This activity was carried out by posyandu cadres in managing Karangrejo Village ILP Posyandu Information System data management. Governance of the implementation of recording and reporting of ILP Posyandu data in Karangrejo Village, management of administrative data and health examination results at ILP Posyandu services in Karangrejo Village, Ngasem District, Kediri Regency.